The Correlation of High School’s Report Values with Grade Point Semester in College’s First Year Using Principal Component Analysis - Astuti, Amalia Yuli; Putri, Nungky Dwi (Jurnal Teknologi Informasi dan Pendidikan, 2024)
The first year in higher education is a crucial time that becomes a fundamental learning momentum for every student. Academic achievements in the college's first year are one of the problems that should be checked. Grade point in the first year becomes one of the success study criteria for the next year at an academic time. In department X of a private university, we found some problems in the courses, such as the mean of graduation time that has not met the target. There is an opinion that the grades of report cards at the time of senior secondary education correlate with the achievement index in the first year of college. This research used Principal Component Analysis (PCA) method and data processing with RStudio version 3.5. The students' data for data processing were from the class of 2015 until 2018. Based on the results, it was found that there was no correlation between student report cards in senior secondary education with grade points for the first and second semesters. However, there was a correlation between report cards scores for Chemistry and Biology so that new student admissions could take report cards scores only for one subject.